CRIMINAL LAW REGULATION OF INFORMATION TURNOVER ON SECURITIES MARKETS IN EUROPE AND CHINA - Brazhnik S. D., Titenkova I. O., Chernov E. E. (Law, Economics and Management, 2023)
the article examines the features of the criminal law protection of the lawful turnover of economic information on the securities market in Europe and China, the authors consider the differences in national legislation regarding the regulation of signs of insider information, the objective side and the subject of the crime.
Keywords: Китай; преступление; crime; transfer; China; инсайдерская информация; рынок ценных бумаг; передача; Европейский Союз; экономическая информация; неправомерный оборот; использование; инсайдер; securities market; European Union; economic information; insider information; illegal turnover; use; insider